Análise de textos didáticos de Matemática: um mapeamento e uma proposta metodológica fundada numa perspectiva hermenêutica - Oliveira, Fábio Donizeti de [UNESP] (Universidade Estadual Paulista (Unesp), Departamento de Matemática, 2010)
This article discusses some methodological possibilities for analyzing textbooks in Mathematics Education. Its starting point was a review - which allowed us to build a general map - of the production developed by consolidated Research Groups that deal with this theme in Brazil. This map allowed us to propose a complementary/alternative guide to analyse textbooks according to a hermeneutical approach.
Analysis of Math textbooks: surveying researches to build a methodological proposal according to a hermeneutical approach
Keywords: Mathematics Education; Methodology; Textbooks